Oddziaływanie ICT na koncentrację uwagi dzieci i młodzieży - różnice opinii uczniów i nauczycieli = The impact of ICT on children and youth attention span - differences in students` and teachers` opinions - Baron-Polańczyk, Eunika (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents an excerpt from a quantitative-qualitative diagnostic-correlational study which aimed to determine students` information competences in the use of ICT tools and methods. It attempts to answer the question about the effects of ICT use by children and youth (the level of significance of new media influence) in the area of ability to concentrate and ignore distracting stimuli. A diagnostic survey method (questionnaire and interview) and statistical methods were used. 2,510 students and 1,110 teachers were surveyed.
Keywords: pedagogika medialna; badania diagnostycznokorelacyjne; kompetencje informacyjne; wykorzystywanie ICT; koncentracja uwagi; media pedagogy; diagnostic-correlational research; informationcompetences; ICT use; attention concentration